2003
DOI: 10.1530/eje.0.1480073
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy of thyroid cancer via retrovirally-driven combined expression of human interleukin-2 and herpes simplex virus thymidine kinase

Abstract: Objective and design: Based on our clinical experience with combined gene therapy of glioblastoma, we developed a retroviral vector expressing two therapeutic genes (i.e. thymidine kinase of herpes simplex virus, HSV-TK, and interleukin-2, IL-2 ) and evaluated its efficiency in vitro and in vivo. Methods: Expression of therapeutic genes in transduced thyroid carcinoma cells was analyzed by realtime RT-PCR. Ganciclovir sensitivity of infected cells was assessed in vitro in thyroid carcinoma cell lines and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…GCV, which is selectively transformed into a toxic metabolite by HSV1-TK, totally eradicated rMTC-TK tumors in 60% of the animals [43]. In a similar study, the expression of both the HSV-TK and the hIL-2 therapeutic genes in infected cells was high and persistent with time and showed that treatment with GCV led to more than 90% tumor growth inhibition and 100% inhibition transduced cells proliferation [44]. Moreover, successful safety and efficacy preclinical studies were conducted in NV 1023 and G207 cell lines, both in vitro and in animal models.…”
Section: Herpes Simplex Virus -1 -Preclinical and Clinical Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…GCV, which is selectively transformed into a toxic metabolite by HSV1-TK, totally eradicated rMTC-TK tumors in 60% of the animals [43]. In a similar study, the expression of both the HSV-TK and the hIL-2 therapeutic genes in infected cells was high and persistent with time and showed that treatment with GCV led to more than 90% tumor growth inhibition and 100% inhibition transduced cells proliferation [44]. Moreover, successful safety and efficacy preclinical studies were conducted in NV 1023 and G207 cell lines, both in vitro and in animal models.…”
Section: Herpes Simplex Virus -1 -Preclinical and Clinical Studiesmentioning
confidence: 77%
“…This retroviral-based vector system exhibited enhanced tumor growth inhibition in animal models [89]. In addition, Barzon et al [44] used a similar retroviral vector system and evaluated its efficiency in vitro and in vivo, following GCV treatment [90]. This study showed an 80% reduction of the size of differentiated thyroid carcinomas [44].…”
Section: Retrovirus -Preclinical and Clinical Studiesmentioning
confidence: 99%
“…Moreover, RNase or other antineoplastic drug administration in the peritumoral area has been successfully used previously for the treatment of rat (Laccetti et al, 1994) or human thyroid tumour cells (Carlomagno et al, 2002;Barzon et al, 2002Barzon et al, , 2003. Obviously, the applicability of RNases in clinical situations and the site of administration of the antitumour molecules would depend largely on the type of the tumour, on its localisation and on the tumour growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…83 Oncolytic viruses (measles, vaccinia, and lentiviruses) expressing the NIS gene have been used to induce cell death as well as facilitate noninvasive imaging and radioiodine therapy. 69,86,94 Combinatorial therapeutic options using small molecule inhibitors such as paclitaxel, 84 bevacizumab, 89 gancliclovir, 95 and aurora kinase inhibitor AZD1152, 82 along with independent virus treatments, have also been evaluated preclinically.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%